2020
DOI: 10.1108/dpm-01-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America

Abstract: PurposeFew people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…dimensions that constitute the agency of community resilience in action enabled dealing with uncertainty due to the unexpected event (as illustrated by Imperiale & Vanclay, 2016 In Haiti, however, the uncertain conditions are structural, embedded in governance of urban services and of the responses to crises. This case supports other studies showing the limits of the application of resilience to describe the response of communities to hazards and structural vulnerabilities and uncertainties (Lizarralde et al, 2020).…”
Section: The Extent Of Embedded Community Resiliencesupporting
confidence: 88%
“…dimensions that constitute the agency of community resilience in action enabled dealing with uncertainty due to the unexpected event (as illustrated by Imperiale & Vanclay, 2016 In Haiti, however, the uncertain conditions are structural, embedded in governance of urban services and of the responses to crises. This case supports other studies showing the limits of the application of resilience to describe the response of communities to hazards and structural vulnerabilities and uncertainties (Lizarralde et al, 2020).…”
Section: The Extent Of Embedded Community Resiliencesupporting
confidence: 88%
“…Some argue that a concept of resilience is also contradictory as well as meaningless in non-Anglophone contexts. Chmutina et al (2020) and Lizarralde et al (2020), for instance, show that ''resilience'' does not reflect local contexts, and its use instead reinforces quasi-imperialist impositions of ideas. Many authors also highlight the current use of the concept, which is predominantly driven by neoliberal ideas of ''growing the wealth of the poor'' (Bracke 2016, p. 52) and using it as a pathway to (re)build the capacity of financial systems and national economies in the aftermath of disasters, thus reinstating the pre-disaster conditions.…”
Section: Resilient Citiesmentioning
confidence: 99%
“…184). Even more critically, Lizarralde et al (2020) in interrogating the strangeness of academic theoretical concepts to lived experiences, suggest that any analysis of the current challenges of climate change, or disasters should not be withdrawn from the struggles of social justice.…”
Section: Towards a Situated And Relational Social Ontology Of Disaster Resiliencementioning
confidence: 99%
“…For example, Enarson (2012), drawing heavily from US-based Women of Color grassroots organising, has suggested that feminist approaches to disasters should acknowledge and work on a structural approach to resilience that emphasises human action finding expression through groups, organisations, coalitions and networks (Enarson, 2012, p. 184). Even more critically, Lizarralde et al (2020) in interrogating the strangeness of academic theoretical concepts to lived experiences, suggest that any analysis of the current challenges of climate change, or disasters should not be withdrawn from the struggles of social justice. Accordingly, Cretney (2019) has suggested a more dynamic and complex understanding of the politics of disasters, drawing attention to the empirical "everyday", when the de/re-politicisation of disaster experience, and interpretations of better futures are constantly contested.…”
mentioning
confidence: 99%